Aflatoxin B1 impairs the growth and development of chicken PGCs through oxidative stress and mitochondrial dysfunction - Ying-Jie Niu; Jun Wu; Wenjie Ren; Guangzheng Liu; Gaoyuan Wu; Yixiu Peng; Dan Zheng; Kai Jin; Qisheng Zuo; Guohui Li; Wei Han; Xiang-Shun Cui; et al. (Ecotoxicology and Environmental Safety)
Aflatoxins harm the reproductive system and gamete development in animals. Primordial germ cells (PGCs) in chickens, as ancestral cells of gametes, are essential for genetic transmission, yet the impact and mechanisms of aflatoxins on them remain elusive. This study systematically investigated the effects of aflatoxin B1 (AFB1) on chicken PGCs and their potential mechanisms using an in vitro culture model. We observed a significant reduction in PGC numbers and an increase in apoptosis levels with AFB1 treatment. Further analysis revealed that AFB1 induced mitochondrial structural and functional abnormalities. Additionally, AFB1 treatment led to increased oxidative stress, lipid peroxidation, ferroptosis, and autophagy in chicken PGCs, ultimately affecting their biological characteristics. Interestingly, we found that the NRF2-mediated antioxidant pathway was activated in AFB1-treated PGCs. Inhibiting NRF2 exacerbated oxidative stress and cell death in PGCs, suggesting NRF2 upregulation plays a protective role under AFB1 regulation. This study illuminates AFB1's toxic effects on chicken PGCs and provides insights into potential mechanisms, establishing a basis for strategies to prevent and treat AFB1's adverse effects on poultry genetic transmission.